2020
DOI: 10.2147/jir.s275785
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Inflammatory Aspect of Male and Female Pattern Hair Loss</p>

Abstract: Male and female pattern hair loss (MPHL and FPHL, respectively), is the most common cause of hair loss affecting nearly 80 million people in the US, yet treatment options remain limited and lacking. As the need for more effective therapeutics remains unmet, this perspective offers a unique angle by directing attention to the inflammatory aspect of MPHL and FPHL. Evidence and implications of inflammation as a characteristic feature of MPHL and FPHL are highlighted through evaluation of clinical and quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 20 publications
1
22
0
2
Order By: Relevance
“…We also found that alopecia increased over time that it mainly affected women, and at 90 days, the proportion of women who suffered alopecia was double that of men. Possible reasons for alopecia in women include inflammation and immunity 22 , 23 and a possible association with emotional distress, 24 which seems plausible given the high proportion of patients in our population who reported sadness and anxiety. These findings indicate that healthcare systems must develop strategies to provide mental health support to COVID-19 survivors with persistent symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…We also found that alopecia increased over time that it mainly affected women, and at 90 days, the proportion of women who suffered alopecia was double that of men. Possible reasons for alopecia in women include inflammation and immunity 22 , 23 and a possible association with emotional distress, 24 which seems plausible given the high proportion of patients in our population who reported sadness and anxiety. These findings indicate that healthcare systems must develop strategies to provide mental health support to COVID-19 survivors with persistent symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…15 We also found that alopecia increased over time, that it mainly affected women, and at 90 days, the proportion of women who suffered alopecia was double that of men. Possible reasons for alopecia in women include inflammation and immunity 20,21 and a possible association with emotional distress, 22 which seems plausible given the high proportion of patients in our population who reported sadness and anxiety.…”
Section: Discussionmentioning
confidence: 92%
“…AGA is positively associated with immune modulation and inflammation, and thus, anti-inflammatory agents can be used to treat the condition [42]. In previous studies, PC was found to reduce the mRNA expressions of TNF-α and IL-6 and to combat chronic nonbacterial prostatitis (a male disease) and arteriosclerosis [39,43].…”
Section: Discussionmentioning
confidence: 99%